Media’s Roles in Reporting Corruption in the Cameroon Development Corporation (CDC) Lands Restitution Process in Fako Division: 2014-2021 - Matute, Jonas Menyoli; Ngange, Kingsley Lyonga; Moki, Stephen Mokondo (Advances in Social Sciences Research Journal, 2022)
Media’s roles in exposing corruption is itemised in the CDC land restitution process in Fako Division of Cameroon, captioned as “The Land Grabbing Saga in Fako Division” by newspapers. Journalism in general and investigative reporting in particular, play a critical role in raising consciousness of and fighting against corruption. It is one of the most effective means of raising public consciousness about corruption. It is in this light that the researchers set out to investigate the actual role played by the media in reporting corruption in the CDC land restitution process. Two qualitative research methods were used to gather data. The first method, the qualitative content analysis, examined contents of four editions of CRTV Buea Press Club radio programme and also exploited contents of some newspapers and online media platforms on corruption in the CDC land restitution process. The second research method, in-depth interview, was used to gather data from some elites of Fako Division, members of the affected villages, journalists who reported on the corruption, some accused persons and CDC officials to ascertain media’s role in exposing corruption. The data reveal that the media played three roles in exposing corruption in the CDC land restitution process: giving information and creating awareness; public education; and prompting peers (other journalists) to also report on corruption. The elites and members of the affected communities attested that some of them were not aware of any corrupt practices until they heard about it on CRTV Buea Press Club and later followed it on newspapers and online media platforms. Findings also show that media investigative reports corroborated evidence to establish the occurrence of corruption in the restitution process. The media exposed this issue by naming and shaming those involved in the corruption (publishing their names and pictures). Amongst other things, this study recommends that the media should be considered as an important tool in the fight against corruption; those interested in exposing corruption in the media should be involved in investigative journalism that will enable them back their reports with documented evidence since corruption is a complex crime. Also, people in public offices should be compelled by law to make available information that is of public interest and good to journalists to enable them expose societal ills (like corruption), especially in public offices and spheres.